Investigation on Social Capital Charecteristics for Community-Based Watershed and Environmental Management: A Case Study of Romphothong Community Thatakieb District Chachoengsao Province - Leknoi, Unruan; Sungkhaman, Sirichet; Niyom, Wicha; Punya, Opas (วารสารวนศาสตร์ไทย, 2022)
The objectives of this research were to investigate the characteristics of social capital towards watershed and environmental management of Romphothong Community, which is the best practice on community-based watershed and environmental management. This study is Ex-post Facto Research in combination with qualitative research and quantitative research. The using Sampling scheme was divided into two parts, qualitative research using snowball sampling, and quantitative research using stratified sampling. The qualitative data was carried out by using content analysis, and quantitative data was analyzed out by descriptive statistics. The results of the study indicated that the characteristics of social capital towards watershed and environmental management were divided into two categories: 1) cognitive social capital: trust, solidarity, norms of conservation, and reciprocity: human and nature, and 2) structural social capital: civil society, engagement in public affairs, groups and networks, participation, empowerment, community organization, establishment of the administrative committee, and information/communication. Keywords: Community-based watershed and environmental management (CBM), Social capital, Watershed, Environment.